The Gift of Mutual Misunderstanding - Ørum, Kristoffer (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2016)
The gifts of mutual misunderstandings is a 3D rendered diagram of the relations between the separate but interconnected "lifeworlds" of programmers, algorithms and users. Based on the proposition that if communication can fail, it will, the diagram combines and misrepresents several theories of communication. It represents an attempt to undermine the perceived authority accorded to the arrows, boxes and pyramids found in so many of the diagrams used to explain the complexities of communication, technology and contemporary life to us.